Exploration of the Distinctive Flower Diversity and their Therapeutic Efficacy from Surajpur District of Chhattisgarh, India (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present research spots light on diversity and therapeutic potentiality of flowers collected from Surajpur district of Chhattisgarh, India. Recently, the traditional knowledge of flowers as therapeutics is gaining increased attention across the globe. The curative potentiality of flowers based on the traditional knowledge of local healers and village dwellers of Surajpur unturned the enigma of enormous efficacy of flowers against several alarming diseases. The different colours of same flower collected from six adjoining tehsils of Surajpur district also divulge that the flower possesses diverse colour and morphology in different areas which is an indicator of rich floral diversity of this region. Despite of immense flora, the region is relatively untouched with special reference to flower diversity and its ethno-medicinal studies. Keeping the above facts into consideration, an attempt was made to focus on the floral diversity and therapeutic efficacy of 68 flowers which covers twenty nine families to cure seventy eight dreadful diseases. The above documentation accord a clear insight on the vast biological and pharmacological potentiality of all the flowers under investigation. Although, the present work is an initial step towards the documentation of local potential flowers having tremendous healing ability with natural, cost effective and without any side effects. However, in time ahead vigorous efforts will be envisaged to extract the active compound from the flowers and to elucidate the complete structure of bioactives using spectral analysis. The above study will lay the strong foundation of floriculture and will definitely pave the path for natural floral medicine as curatives in years ahead.